Pengaruh Penggunaan Buku Cerita Rakyat Berbasis Digital terhadap Membaca Pemahaman Murid Kelas IV SDN 1 Puyung dan SDN 2 Puyung - Elisya Laili Rahmadani; Nurhasanah; Gozin Najah Rusyada (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low reading comprehension skills of elementary school students, particularly in understanding the content of texts, identifying main ideas, and retelling the content of texts. One alternative to address this issue is the use of digital-based folk tale books, which present reading material in a more engaging and interactive manner. This study aims to determine the effect of using digital-based folk tale books on the reading comprehension of fourth-grade students at SDN 1 Puyung and SDN 2 Puyung. This study employs a quantitative approach with a quasi-experimental design. The research sample consisted of 70 students, comprising 37 students in the experimental class and 33 students in the control class. Data collection was conducted through tests and observations, while data analysis utilized normality tests, homogeneity tests, N-Gain tests, and Mann-Whitney tests. The results showed that the use of digital-based folk tale books had a significant effect on students’ reading comprehension, as indicated by an Asymp.Sig. (2-tailed) value of 0.012, which is less than 0.05 (0.012 < 0.05); therefore, H0 was rejected and Ha was accepted. In addition, the average N-Gain score for the experimental class was 0.5075, categorized as moderate, while that for the control class was 0.2110, categorized as low. Thus, the use of digita-based folklore books is quite effective in developing elementary school students' reading comprehension skills.